Energy generation by extracellular aldose oxidation in N2-fixing Gluconacetobacter diazotrophicus - Luna, María Flavia (2002)
Gluconacetobacter diazotrophicus PAL3 was grown in a chemostat with N2 and mixtures of xylose and gluconate. Xylose was oxidized to xylonate, which was accumulated in the culture supernatants. Biomass yields and carbon from gluconate incorporated into biomass increased with the rate of xylose oxidation. By using metabolic balances it is demonstrated that extracellular xylose oxidation led N2-fixing G. diazotrophicus cultures to increase the efficiency of energy generation.